Porous carbon graphite plate and preparation method thereof

Through micro-heat pressing molding and high-pressure electrostatic melting 3D printing technology, high-strength, high-density porous carbon graphite plates were prepared, which solved the problems of low density and uneven pore distribution in traditional methods, and improved the stability and efficiency of air float transmission.

CN119638484APending Publication Date: 2025-03-18CHINA THREE GORGES UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411905455.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

It is difficult to prepare porous carbon graphite plates that take into account the characteristics of high strength, high density and high porosity. Especially in the air-floating transmission device of glass substrates, the size of the holes and the uniformity of the distribution have a great impact on the transmission stability.

Method used

Micro-heat pressing process and high-pressure electrostatic melting 3D printing technology are used to react Si in the mixed powder with resin carbon to generate SiC to improve material strength; pores are formed using meso-phase carbon microspheres and phenolic resins to improve porosity; at the same time, the pore distribution and number are regulated through the design of the organic matter network.

Benefits of technology

A porous carbon graphite plate with high strength, high density and high porosity was prepared. The pore size and distribution were controllable, which solved the problems of low density, uneven pore distribution and poor mechanical properties in traditional methods, and improved the stability and efficiency of air float transmission.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638484A_ABST
    Figure CN119638484A_ABST
Patent Text Reader

Abstract

The invention discloses a porous carbon graphite plate and a preparation method thereof. The porous carbon graphite plate is prepared from natural flake graphite powder, high-purity silicon powder, mesocarbon microbeads and resin carbon. The preparation process of the porous carbon graphite plate comprises the process links of mixed powder preparation, layer unit pre-forming, high-voltage electrostatic melting 3D printing of an organic matter screen plate, multiple times of repetition, heating and pressurizing secondary forming to obtain a porous carbon graphite plate biscuit, high-temperature sintering to construct a micropore channel, ultrasonic cleaning, drying and the like. The preparation method of the porous carbon graphite plate provided by the invention has the advantages of simplicity, low cost, stability, high efficiency and the like, and is suitable for preparing the porous carbon graphite plate; the obtained porous carbon-graphite plate has the characteristics of high strength, high density, high porosity, controllable pore size and distribution and the like, and can be used for an air floatation transmission device in scenes of supporting and transporting liquid crystal glass substrates and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention provides a porous carbon graphite plate and a preparation method thereof, belonging to the technical field of inorganic non-metal forming, and specifically relates to the development and application of a high-strength, high-density and high-porosity porous carbon graphite plate. Background Art

[0002] Liquid crystal glass substrate is a thin glass sheet produced by float process with extremely flat surface. It is located at the bottom layer of liquid crystal display and mainly plays the role of supporting liquid crystal panel. As the glass substrate of liquid crystal display develops towards large-scale and ultra-thin, the defect detection requirements of liquid crystal display glass substrate are getting higher and higher. The use of non-contact, low-friction, high-precision air floating transmission device has become a consensus in the flat plate conveying industry. Figure 2 As shown in the figure, the working principle of the air flotation transmission device is to introduce constant pressure gas into the gap between the workbench and the glass substrate through the throttling device to form a layer of air film with certain rigidity and bearing capacity, and to suspend and transport the glass substrate. It has the advantages of almost no wear, high precision, and no pollution, which can reduce costs and improve the yield rate. As an important component of the air flotation transmission device, the size of the internal pores of the porous carbon graphite plate, its distribution uniformity, connectivity, and pressure resistance have a great influence on the air flotation transmission state. In air flotation transmission, the pores of the porous carbon graphite plate are nano-scale pores. If the pores are too large, the number of pores per unit volume is insufficient, the distribution uniformity will be unreasonable, the air pressure will be uneven, and the mechanical properties will deteriorate, and the transmission process will be unstable; if the open porosity is too low, the air pressure will pass through the graphite plate, and the gas volume is insufficient, making it difficult to support the glass substrate. If the open porosity is too high, the mechanical properties are insufficient and it is difficult to withstand the air pressure, which has a great impact on the stability of the transmission.

[0003] How to take into account the pore characteristics and mechanical properties of porous carbon graphite plates is a key technical difficulty. At present, the main methods for preparing porous carbon graphite plates are: foaming method, screen method, and 3D printing method. The raw materials of the foaming method are generally polymers and various asphalts. According to different foaming methods, they are generally divided into physical foaming method and chemical foaming method. The steps of the physical foaming method are to place the raw materials in an autoclave, heat them to a temperature slightly higher than their softening point at a constant rate, and at the same time add inert gases such as nitrogen to achieve a high-pressure environment. Due to the increase in temperature, the gas expands, and the raw materials are foamed into foam after decompression; then the temperature is increased, and the foam is oxidized, fixed, carbonized, and graphitized. The chemical foaming method uses chemical methods to produce gas for foaming, such as heating the chemical foaming agent added to the raw material to decompose and release gas for foaming, or using the gas released by the chemical reaction between the raw material components to foam, and then the steps are roughly the same as the physical foaming method, and oxidation fixation, carbonization, and graphitization are carried out. The density of porous carbon graphite produced by foaming method is low, usually less than 0.8 g / cm 3, and the pore distribution is poor and the arrangement characteristics are uncontrollable. The mesh method is to first introduce an organic carbon source (such as formaldehyde, phenol, sucrose, etc.) into the pores of an inorganic mesh material (such as silica gel, aluminosilicate, zeolite, etc. with a mesh structure) to obtain an organic / inorganic composite. The composite is polymerized, carbonized or chemically vapor deposited (during which a series of physical and chemical processes occur in the mesh pores) to obtain a carbon / mesh composite, and then the mesh is removed by a suitable chemical method to obtain a porous carbon with a regular and orderly structure; this method has a long cycle, high cost, and the porous carbon generated has low strength and is difficult to withstand high air pressure. The 3D printing method uses artificial graphite powder, spherical graphite powder, and thermosetting phenolic resin powder as raw materials, and uses selective laser sintering molding technology to quickly prepare porous carbon preforms, but the porous carbon formed by this method has low density, large pores, poor mechanical properties, and uncontrollable porous characteristics.

[0004] In summary, due to the particularity of the porous carbon graphite plate in the air flotation transmission device of the glass substrate, there is currently a lack of effective process methods in China, and it is difficult to prepare a porous carbon graphite plate with high strength, high density and high porosity. Summary of the invention

[0005] In view of the current difficulties in preparing high-strength, high-density, nano-level porous carbon graphite plates and ensuring uniform pore size distribution, the present invention provides a high-strength, high-density, high-porosity, controllable pore size and distribution porous carbon graphite plate and a preparation method thereof. The inventive concept and technical principles are as follows: (1) The process selected is a micro hot pressing process. Since the thickness of the layer unit and its compression distance are controllable, the gas influence is eliminated by stacking and compacting the layer units layer by layer, thereby improving the density of the porous graphite plate; the powder mixing method is wet mixing, which makes the interlayer bonding force better during molding and the molding effect better; adding a certain amount of Si will react with the resin carbon to generate SiC during the high-temperature sintering process, thereby improving the strength of the porous graphite plate; by introducing the mesophase carbon microspheres, due to the presence of β-resin, volatiles will be generated during the high-temperature sintering process, so they will shrink and fill the pores, which can effectively improve the density and mechanical properties of the porous graphite plate; (2) If Figure 3 As shown, spherical mesophase carbon microspheres and flake graphite are mixed and hot-pressed to form micropores; at the same time, phenolic resin will form some pores during the carbonization process, thus increasing the porosity of the porous carbon graphite plate; (3) High-voltage electrostatic melting 3D printing technology is used to print ablative organic mesh plates. During the carbonization process, due to the difference in pyrolysis temperature between the organic network and the phenolic resin, the constructed two-dimensional organic network has been completely pyrolyzed and continuous holes have been formed before the phenolic resin is pyrolyzed in large quantities. First, these continuous holes can be used as exhaust channels to improve the problem of easy cracking of graphite parts during carbonization. Second, the shape and number of the organic network can be changed to achieve the control of hole distribution, number, and pore size. Third, after the organic matter is completely pyrolyzed, resin carbon will be generated, and the resin carbon will react with Si to generate SiC, which will further improve the mechanical properties of the material and solve the problems of hole size, uneven distribution, and low molding efficiency.

[0006] A method for preparing a high-strength, high-density, high-porosity porous carbon graphite plate comprises the following specific steps: (1) Preparation of mixed powder: High-purity silicon powder, natural flake graphite powder, mesophase carbon microspheres, and liquid phenolic resin are mixed in a kneader. After the mixture is evenly mixed, the mixture is taken out and dried, crushed, and sieved to obtain a mixed powder. (2) Layer unit preforming: the mixed powder is spread flat in a mold, preheated and pressurized to obtain a layer unit preform; (3) High-voltage electrostatic melting 3D printing of organic stencil: A two-dimensional organic stencil is constructed on the layer unit using a high-voltage electrostatic melting 3D printer to obtain a layer unit preform with an organic stencil distributed on the surface; (4) Heating and pressurizing to obtain a porous carbon graphite plate blank: Repeating the above steps (2) and (3) multiple times, accumulating the layer unit preform containing the organic mesh to a certain height, heating and pressurizing for a second time, and obtaining a porous carbon graphite plate preform blank; (5) High-temperature sintering to form microporous channels: The porous carbon graphite plate preform blank is placed in a vacuum sintering furnace for high-temperature sintering treatment to ablate the organic mesh to generate silicon carbide and obtain a porous carbon graphite plate; (6) Ultrasonic cleaning: Use an ultrasonic cleaner to clean the porous carbon graphite plate to remove the residues left after ablation of the organic matter screen; (7) Drying: Use a drying oven to dry to obtain a porous carbon graphite plate.

[0007] The mixed powder in step (1) comprises natural flake graphite powder of 200-500 mesh, carbon content greater than 98%, mass fraction of 30-60 wt.%, high-purity silicon powder of 200-500 mesh, chemical purity of 99%, mass fraction of 15-35 wt.%, mesophase carbon microspheres of 600-900 mesh, mass fraction of 15-25 wt.%, and liquid phenolic resin with a concentration of 40-65% and a mass fraction of 10-30 wt.%.

[0008] The kneading process working parameters in step (1) are as follows: when the mixed powder is kneaded, anhydrous ethanol needs to be added, and the amount added is: liquid phenolic resin and anhydrous ethanol are added according to a mass ratio of 1:3-5, the kneading machine speed is 50-100 r / min, and the kneading time is 2-4 h.

[0009] The drying, crushing and sieving in step (1) means that the powder taken out after mixing is placed in a drying box at a drying temperature of 60-70°C. The dried powder is then crushed by a crusher, and finally sieved with a 500-800 mesh screen, and the sieved material is taken to obtain a mixed powder.

[0010] The preforming process parameters of the layer unit in step (2) are as follows: the density of the layer unit is controlled within 1.3-1.5 g / cm by controlling the descending distance of the pressure head. 3 , thickness is controlled at 2~4 mm, forming pressure is not less than 100 MPa, holding time is 5~10min, and preheating temperature is 80~90℃.

[0011] The high-voltage electrostatic melting 3D printing organic stencil in step (3) refers to printing an ablative two-dimensional organic stencil on a layer unit by a high-voltage electrostatic melting 3D printer, wherein the material is polylactic acid PLA or polycaprolactone PCL, and the diameter thereof is 200-1000 nm. The process parameters of the high-voltage electrostatic melting 3D printer are: receiving platform temperature 4-21°C, printing speed 10-70 mm / s, high voltage 1-10 kV can be applied, nozzle temperature 30°C-210°C, and heating speed ≤6 min.

[0012] The heating and pressurizing secondary molding in step (4) to obtain the porous carbon graphite plate blank means that after the exhaust network is constructed on the layer unit, the layer unit is repeatedly micro-hot pressed to alternately prepare the layer unit and the exhaust network. After accumulating to a certain height, the electromagnetic pressure head is used for impact molding, the heating temperature is 110-160 ° C, the molding pressure is 150-180MPa, and the molding density is not less than 1.90 g / cm 3 The impact speed of the electromagnetic pressure head is 250-300 times / min.

[0013] The high-temperature sintering technical parameters in the step (5) are as follows: the solidified sample is transferred into a carbonization furnace for high-temperature sintering treatment (first evacuating to about -0.1 MPa, heating to 380°C at a heating rate of 110-190°C / h, keeping warm for 0.5 h, then heating to 1100°C at a heating rate of 50-120°C / h, and filling with 99% pure nitrogen at 250-400°C, finally heating to 1500-1700°C at a heating rate of 90-170°C / h, keeping warm for 1-4 h, and cooling to room temperature with the furnace) and taken out to obtain a porous carbon graphite plate.

[0014] The drying technical parameters in step (6) are as follows: the porous carbon graphite plate is placed in an oven for drying at a drying temperature of 60-70°C.

[0015] The above technical method has the following advantages: 1. Compared with the traditional method, the process selected is the micro hot pressing molding process. By preparing the preform in advance, the phenomenon that the gas cannot be effectively removed from the mold during one hot pressing molding is avoided. It not only has a simple process flow and low cost, but also makes the product more stable and efficient; the powder mixing method is wet mixing, which makes the interlayer bonding during molding better and the molding effect better.

[0016] 2. During the sintering process, due to the difference in pyrolysis temperature between the organic network and the phenolic resin, the constructed two-dimensional organic network has been completely pyrolyzed and formed continuous holes before the phenolic resin is pyrolyzed in large quantities. The continuous holes effectively avoid the crack defects caused by the difficulty of gas escape during the carbonization of the phenolic resin, and increase the heating rate, thereby improving production efficiency.

[0017] 3. Use high-voltage electrostatic melting 3D printing technology to print ablative organic stencils. By changing the shape and quantity of the organic network, the distribution, quantity and pore size of the holes can be regulated. The organic matter is selected to be polylactic acid PLA or polycaprolactone PCL with a low melting point and which will generate resin carbon after pyrolysis. The resin carbon formed by the pyrolysis of the organic matter will react with Si to generate SiC, which will further improve the mechanical properties of the material; it solves the problems of hole size, uneven distribution and low molding efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The present invention will be further described below in conjunction with the accompanying drawings: Figure 1 Process flow chart for preparing porous carbon graphite plates.

[0019] Figure 2 Schematic diagram of the working principle of the air flotation transmission device.

[0020] Figure 3 This is a schematic diagram of the combination of natural flake graphite powder and mesophase carbon microspheres.

[0021] Figure 4 It is a schematic diagram of the air permeable channel structure of a porous carbon graphite plate.

[0022] Figure 5 This is a schematic diagram comparing the molding with (A) adding an exhaust network and without (B) adding an exhaust network.

[0023] Figure 6 This is a schematic diagram comparing the forming pressure with adjustment (A) and without adjustment (B). DETAILED DESCRIPTION

[0024] Example 1 A method for preparing a high-strength, high-density, high-porosity porous carbon graphite plate, such as Figure 1 As shown, the porous carbon graphite plate is composed of natural flake graphite powder, high-purity silicon powder, mesophase carbon microspheres and liquid phenolic resin, wherein the volume proportion of natural flake graphite powder is 40 wt.% (200 mesh), the volume proportion of high-purity silicon powder is 25 wt.% (200 mesh), the volume proportion of mesophase carbon microspheres is 20 wt.% (650 mesh), and the volume proportion of liquid phenolic resin is 15 wt.% (50 mass%).

[0025] The specific preparation steps are as follows: (1) Preparation of mixed powder: 25 wt.% (200 mesh) of high-purity silicon powder, 40 wt.% (200 mesh) of natural flake graphite powder, 20 wt.% (650 mesh) of mesophase carbon microspheres, and 15 wt.% (50 mass%, liquid phenolic resin and anhydrous ethanol in a mass ratio of 1:3) were put into a kneader and mixed. The kneader speed was 50 r / min, and the kneading time was 4 h. The powder taken out after mixing was put into a drying box, and the drying temperature was 60~70 ℃. Then the dried powder was crushed by a crusher, and finally sieved with a 500-mesh screen, and the sieved material was taken to obtain a mixed powder.

[0026] (2) Layer unit preforming The mixed powder is spread flat in the mold, and the density of the layer unit is controlled at 1.3 g / cm by controlling the descending distance of the pressure head. 3 , the unit layer thickness is 4 mm (the compression distance is controlled to be 4 mm according to the unit layer thickness of 4 mm), the forming pressure is 100 MPa, the holding time is 10 min, the preheating temperature is 90 ° C, and a layer unit preform is obtained.

[0027] (3) High-voltage electrostatic melting 3D printing organic stencil Using high-voltage electrostatic melting 3D printing organic stencils refers to printing ablative two-dimensional organic stencils (such as Figure 4 As shown in the figure, the material selected is polylactic acid PLA, and its diameter is 400 nm. Among them, the process parameters of the high-voltage electrostatic melting 3D printer are: receiving platform temperature 6 ℃, printing speed 15 mm / s, high voltage 5 kV can be applied, nozzle temperature 150 ℃, heating rate ≤ 6 min, and a layer unit preform with an organic stencil distributed on the surface is obtained.

[0028] (4) Heating and pressing for secondary molding to obtain porous carbon graphite sheet blank The preparation of porous carbon graphite blanks refers to the repeated micro-hot pressing of layer units after the exhaust network is constructed on the layer units. The layer units and the exhaust network are prepared alternately. After accumulating to a certain height, the electromagnetic pressure head is used for impact molding. The heating temperature is 140 °C, the molding pressure is 160 MPa, and the molding density is 1.92 g / cm 3 The impact speed of the electromagnetic pressing head is 250 times / min, and the porous carbon graphite plate preform blank is obtained after pressing.

[0029] (5) High temperature sintering to form microporous channels The porous carbon graphite preform blank was transferred into a carbonization furnace for high-temperature sintering treatment (first evacuated to about -0.1 MPa, heated to 380 °C at a heating rate of 120 °C / h, kept warm for 0.5 h, then heated to 1100 °C at a heating rate of 100 °C / h, and filled with 99% pure nitrogen at 350 °C, finally heated to 1600 °C at a heating rate of 100 °C / h, kept warm for 4 h, and cooled to room temperature with the furnace) and taken out to obtain a porous carbon graphite plate.

[0030] (6) Ultrasonic cleaning: Use an ultrasonic cleaning machine to clean the porous carbon graphite plate and remove floating dust; (7) Drying: The porous carbon graphite plate is placed in an oven for drying at a temperature of 70°C to obtain a porous carbon graphite plate.

[0031] The experimental results show that the size of the porous carbon graphite plate prepared by this process is 500×100×10 mm and the density is 1.92 g / cm 3 , the open porosity is 24%, the average pore diameter is 350 nm, the flexural strength is 73 MPa, the compressive strength is 92 MPa, and the surface is complete, smooth and free of defects.

[0032] Example 2 A high-strength, high-density, high-porosity porous carbon graphite plate and a preparation method thereof. The porous carbon graphite plate is composed of natural flake graphite powder, high-purity silicon powder, mesophase carbon microspheres and liquid phenolic resin, wherein the volume proportion of natural flake graphite powder is 40 wt.% (200 mesh), the volume proportion of high-purity silicon powder is 25 wt.% (200 mesh), the volume proportion of mesophase carbon microspheres is 20 wt.% (650 mesh), and the volume proportion of liquid phenolic resin is 15 wt.% (50 mass%).

[0033] The specific preparation steps are as follows: (1) Preparation of mixed powder: 25 wt.% (200 mesh) of high-purity silicon powder, 40 wt.% (200 mesh) of natural flake graphite powder, 20 wt.% (650 mesh) of mesophase carbon microspheres, and 15 wt.% (50 mass%, liquid phenolic resin and anhydrous ethanol in a mass ratio of 1:3) were put into a kneader and mixed. The kneader speed was 50 r / min, and the kneading time was 4 h. The powder taken out after mixing was put into a drying box, and the drying temperature was 70 °C. Then the dried powder was crushed by a crusher, and finally sieved with a 500-mesh screen, and the sieved material was taken to obtain a mixed powder.

[0034] (2) Layer unit preforming The mixed powder is spread flat in the mold, and the density of the layer unit is controlled at 1.4 g / cm by controlling the descending distance of the pressure head. 3 , the unit layer thickness is 2 mm (the compression distance is controlled to be 2 mm according to the unit layer thickness of 2 mm), the forming pressure is 100 MPa, the holding time is 10 min, the preheating temperature is 90 ° C, and a layer unit preform is obtained.

[0035] (3) High-voltage electrostatic melting 3D printing organic stencil Using high-voltage electrostatic melting 3D printing organic stencils refers to printing ablative two-dimensional organic stencils (such as Figure 4 As shown in the figure, the material selected is polylactic acid PLA, and its diameter is 400 nm. Among them, the process parameters of the high-voltage electrostatic melting 3D printer are: receiving platform temperature 6 ℃, printing speed 15 mm / s, high voltage 5 kV can be applied, nozzle temperature 150 ℃, heating rate ≤ 6 min, and a layer unit preform with an organic mesh plate distributed on the surface is obtained.

[0036] (4) Heating and pressing for secondary molding to obtain porous carbon graphite sheet blank The preparation of porous carbon graphite blanks refers to the repeated micro-hot pressing of layer units after the exhaust network is constructed on the layer units. The layer units and the exhaust network are prepared alternately. After accumulating to a certain height, the electromagnetic pressure head is used for impact molding. The heating temperature is 150℃, the molding pressure is 170 MPa, and the molding density is 1.93 g / cm 3 The impact speed of the electromagnetic pressing head is 260 times / min, and the porous carbon graphite plate preform blank is obtained after pressing.

[0037] (5) High temperature sintering to form microporous channels The porous carbon graphite preform blank was transferred into a carbonization furnace for high-temperature sintering treatment (first evacuated to about -0.1 MPa, heated to 380 °C at a heating rate of 160 °C / h, kept warm for 0.5 h, then heated to 1100 °C at a heating rate of 110 °C / h, and filled with 99% pure nitrogen at 350 °C, finally heated to 1600 °C at a heating rate of 90 °C / h, kept warm for 4 h, and cooled to room temperature with the furnace) and taken out to obtain a porous carbon graphite plate.

[0038] (6) Ultrasonic cleaning: Use an ultrasonic cleaning machine to clean the porous carbon graphite plate and remove floating dust; (7) Drying: The carbon graphite plate is placed in an oven for drying at a temperature of 70°C to obtain a porous carbon graphite plate.

[0039] The experimental results show that the size of the porous carbon graphite plate prepared by this process is 400×100×8 mm and the density is 1.93 g / cm 3 , open porosity is 23%, average pore diameter is 340 nm, bending strength is 75 MPa, and compressive strength is 94 MPa. The surface is complete, smooth and free of defects.

[0040] Example 3 It is basically the same as Example 2, except that the diameter of the organic PLA is adjusted to 300 nm, and the size of the porous carbon graphite plate is adjusted to 200×100×6 mm.

[0041] The experimental results show that the size of the porous carbon graphite plate prepared by this process is 200×100×6 mm and the density is 1.95 g / cm 3 , open porosity is 22%, average pore diameter is 320 nm, bending strength is 76 MPa, and compressive strength is 96 MPa. The surface is complete, smooth and free of defects.

[0042] Example 4 It is basically the same as Example 3, except that when mixing the powders, the proportion of the mesophase carbon microspheres is adjusted to 25 wt.%, the proportion of the natural graphite flakes is adjusted to 35 wt.%, and the size of the porous carbon graphite plate is adjusted to 200×100×4 mm.

[0043] The experimental results show that the size of the porous carbon graphite plate prepared by this process is 200×100×4 mm and the density is 1.97 g / cm 3 , open porosity is 20%, average pore diameter is 310 nm, bending strength is 78 MPa, and compressive strength is 100 MPa. The surface is complete, smooth and free of defects.

[0044] Example 5 It is basically the same as Example 3, except that the step of "high-voltage electrostatic melting 3D printing organic mesh" is not performed, resulting in the exhaust network not being formed in the end.

[0045] The experimental results show that the size of the porous carbon graphite plate prepared by this process is 200×100×6 mm and the density is 1.82 g / cm 3 , open porosity is 22%, average pore diameter is 330 nm, flexural strength is 42 MPa, and compressive strength is 63 MPa. Figure 5 As shown, the surface is incomplete, not smooth and has cracks.

[0046] Example 6 It is basically the same as Example 3, except that when performing "layer unit preforming", the forming pressure is adjusted to 200 MPa.

[0047] The experimental results show that the size of the porous carbon graphite plate prepared by this process is 200×100×6 mm and the density is 1.80 g / cm 3 The open porosity is 23%, the average pore size is 326 nm, the bending strength is 40 MPa, and the compressive strength is 60 MPa. The surface is complete, smooth and free of defects. Figure 6 As shown, the surface is extremely incomplete, not smooth and has crushing phenomena.

Claims

1. A method for preparing a porous carbon graphite plate, characterized in that: The preparation process is as follows: (1) Preparation of mixed powder: high-purity silicon powder, natural flake graphite powder, mesophase carbon microspheres, and liquid phenolic resin are mixed in a kneader, and after being mixed evenly, the mixture is taken out and dried, crushed, and sieved to obtain a mixed powder; (2) Layer unit preforming: the mixed powder is spread flat in a mold, preheated and pressurized to obtain a layer unit preform; (3) High-voltage electrostatic melting 3D printing of organic stencil: A two-dimensional organic stencil is constructed on the layer unit using a high-voltage electrostatic melting 3D printer to obtain a layer unit preform with an organic stencil distributed on the surface; (4) Heating and pressurizing to obtain a porous carbon graphite plate blank: Repeat the above steps (2) to (3) multiple times, accumulate the layer unit preform containing the organic mesh to a certain height, and heat and pressurize it again to obtain a porous carbon graphite plate preform blank; (5) High-temperature sintering to form microporous channels: The porous carbon graphite preform blank is placed in a vacuum sintering furnace for high-temperature sintering to ablate the organic mesh to generate silicon carbide and obtain a porous carbon graphite plate; (6) Ultrasonic cleaning: Use an ultrasonic cleaner to clean the porous carbon graphite plate to remove the residues left after ablation of the organic matter screen; (7) Drying: Use a drying oven to dry to obtain a porous carbon graphite plate.

2. The method for preparing a porous carbon graphite plate according to claim 1, characterized in that: The mixed powder in step (1) comprises natural flake graphite powder of 200-500 mesh, carbon content greater than 98%, mass fraction of 30-60 wt.%, high-purity silicon powder of 200-500 mesh, chemical purity greater than 99%, mass fraction of 15-35 wt.%, mesophase carbon microspheres of 600-900 mesh, mass fraction of 15-25 wt.%, and liquid phenolic resin with a concentration of 40-65% with a mass fraction of 10-30 wt.%.

3. The method for preparing a porous carbon graphite plate according to claim 1, characterized in that: The working parameters of the kneading process in step (1) are as follows: when the mixed powder is kneaded, anhydrous ethanol is added in an amount of: liquid phenolic resin and anhydrous ethanol are added in a mass ratio of 1:3-5, the kneading machine speed is 50-100 r / min, and the kneading time is 2-4 h.

4. The method for preparing a porous carbon graphite plate according to claim 1, characterized in that: The drying, crushing and sieving in step (1) refers to: putting the powder taken out after mixing evenly into a drying box, the drying temperature of which is 60-70°C, then crushing the dried powder by a crusher, and finally sieving with a 500-800 mesh screen, taking the sieved material to obtain a mixed powder.

5. The method for preparing a porous carbon graphite plate according to claim 1, characterized in that: The preforming process parameters of the layer unit in step (2) are as follows: the density of the layer unit is controlled within 1.3-1.5 g / cm by controlling the descending distance of the pressure head. 3 , thickness is controlled at 2~4 mm, forming pressure is not less than 100 MPa, holding time is 5~10 min, and preheating temperature is 80~90℃.

6. The method for preparing a porous carbon graphite plate according to claim 1, characterized in that: The high-voltage electrostatic melting 3D printed organic stencil in step (3) refers to printing an ablative two-dimensional organic stencil on a layer unit by a high-voltage electrostatic melting 3D printer, wherein the material is selected from polylactic acid PLA or polycaprolactone PCL, and the diameter thereof is 200-10000 nm; wherein the process parameters of the high-voltage electrostatic melting 3D printer are: receiving platform temperature 4-21°C, printing speed 10-70 mm / s, applied high voltage 1-10 kV, nozzle temperature 30°C-210°C, and heating rate ≤6 min.

7. The method for preparing a porous carbon graphite plate according to claim 1, characterized in that: The heating and pressurizing secondary molding in step (4) to obtain the porous carbon graphite sheet blank means that after the exhaust network is constructed on the layer unit, the layer unit micro-hot pressing molding and the exhaust network are repeated alternately prepared, and after accumulating to a certain height, the electromagnetic pressure head is used for impact molding, the heating temperature is 110-160 ° C, the molding pressure is not less than 150-180MPa, and the molding density is not less than 1.90 g / cm 3 The impact speed of the electromagnetic pressure head is 250-300 times / min.

8. The method for preparing a porous carbon graphite plate according to claim 1, characterized in that: The high-temperature sintering technical parameters in the step (5) are as follows: the solidified sample is transferred into a carbonization furnace for high-temperature sintering treatment, first evacuated to -0.1MPa, heated to 380°C at a heating rate of 110-190°C / h, kept warm for 0.5-1h, then heated to 1100°C at a heating rate of 50-120°C / h, and filled with 99% pure nitrogen at 250-400°C, finally heated to 1500-1700°C at a heating rate of 90-170°C / h, kept warm for 1-4h, cooled to room temperature with the furnace, taken out, and a porous carbon graphite plate is obtained.

9. The method for preparing a porous carbon graphite plate according to claim 1, characterized in that: The drying technical parameters in step (6) are as follows: placing the porous carbon graphite plate in an oven for drying at a drying temperature of 60-70°C.

10. The porous carbon graphite plate prepared by the method according to any one of claims 1 to 9, characterized in that: The porous carbon graphite plate is formed by connecting natural flake graphite powder with silicon carbide, mesophase carbon microspheres and resin carbon, with an average pore size of 200-10000 nm, an open porosity of not less than 15%, and a density of not less than 1.90 g / cm 3 , withstand 0.25 Mpa air pressure shock.

Citation Information

Patent Citations

  • Preparation method of high-strength and high-density graphite casting mold material

    CN117602940A

  • Preparation method of high-thermal-conductivity porous graphite skeleton

    CN117602949A

  • High-strength high-thermal-conductivity graphite ceramic composite material and preparation method thereof

    CN117682858A

  • Preparation method of lightweight high-strength high-density graphite skeleton

    CN117964391A